Digital Cubic Space as a New Economic Augmented Reality - Kraus, N.M.; Kraus, K.M.; Andrusiak, N.O. (Science and Innovation, 2024)
Introduction. Digital cubic space implies the formation of new economic augmented reality into socio-economic life at various levels of economic aggregation, thus accelerating the digitalization of Ukrainian economy. Problem Statement. Taking into account the existing R&D developments in the field of knowledge of digital economy, not yet learned is transformation of digital technologies at the enterprise, based on the introduction of innovative changes such as BlockChain, FinTech, front office, back office, middle office, omni-business. Purpose. Disclosure of the content of digital cubic space as a new economic complemented reality and presentation of its characteristics through the knowledge of qualitative functioning of FinTech’s and the peculiarities of BlockChain, the formation of which occurs during the digitization of the economy, for the purpose of creation of digital products/services. Materials and methods. Based on the dialectic, system and matrix methods, digital cubic space becoming a new supplemented reality during the digitization of Ukrainian economy has been studied. A comparison of innovative development ratings that affects the speed of digitalization in individual countries around the world has been used. Results. By analogy with the construction of well-known Rubik’s cube, author’s proved that the formation of an efficiently functioning digital economy is possible in conditions of simultaneous harmonic relations “science-business-government-education” resulting in a special environment — digital cubic space of new economic augmented reality. The FinTech 1.0, FinTech 2.0, FinTech 3.0, FinTech 3.5 technologies have been distinguished. The author’s interpretation of the content of digital economy and the category “digital cubic space” has been proposed. The distinction between virtual, extended, expanded, improved, enriched, mixed realities is indicated. Conclusions. Digital cubic space forms a new economic augmented reality at the expense of digital discoveries, the volume of the market of digital products/services. Such institutions are included in the driving forces of digital cubic space: digital hubs, digital platforms, digital currency, FinTech, RegTech, SupTech, new industrial technology Industry 4.0.